Retinal thickness is indicative of visual loss in patients with occipital lobe infarction - Bai, Xueling; Cao, Le; Wang, Hang; Kwapong, William Robert; Yan, Yuying; Liu, Guina; Liu, Junfeng; Hu, Fayun; Wu, Bo (Frontiers in Neurology, 2025)
PurposeWe explored the relationship between retinal thicknesses and vessels using optical coherence tomography angiography (OCT)/ OCT angiography (OCTA) and clinical outcomes in occipital lobe infarction (OI).MethodsA total of 52 OI patients and 105 controls underwent macular OCT/OCTA scans covering a 6 × 6 mm2 area around the fovea. The retinal nerve fiber layer (RNFL), ganglion cell-inner plexiform layer (GCIPL), superficial vascular complex (SVC), and deep vascular complex (DVC) were measured using the OCT/OCTA tool. All participants underwent a visual acuity examination.ResultsOI patients showed reduced GCIPL thickness and lower SVC density but higher DVC density (all p < 0.001) compared to the controls, both in the whole area and across the four sectors. Eyes ipsilateral or contralateral to infarction showed reduced GCIPL thickness and lower SVC density (all p < 0.05). The GCIPL thickness was significantly correlated with the infarct diameter and visual acuity (both p < 0.05), while the SVC density was also significantly correlated with the infarct diameter (p = 0.002). The visual acuity showed a significant association with the infarct diameter (p < 0.001), and the reduction of the GCIPL partially mediated this effect (a proportion of the mediated effect at 15.17%, p = 0.028).ConclusionGCIPL thinning may account for the effect of infarct diameter on visual acuity in OI patients. Future prospective studies are needed to assess OCT/OCTA as a potential marker of visual loss in OI.